(untitled) (Web of Teachers: Inderscience Research, 2026)
The article discusses the theoretical and practical possibilities of using modern pedagogical technologies in teaching plant protection science. The effectiveness of interactive methods - problem-based learning, cluster, conceptual map, laboratory modeling, STEAM approach, digital simulators, game technologies and competency-based tasks is scientifically analyzed. Also, 9 educational games that can be used in such areas as phytopathology, entomology, and weed control are given with a methodological description.